2016
DOI: 10.3389/fpsyg.2016.01445
|View full text |Cite
|
Sign up to set email alerts
|

Inspecting the Dangers of Feeling like a Fake: An Empirical Investigation of the Impostor Phenomenon in the World of Work

Abstract: To investigate the link between the impostor phenomenon (IP), career self-management (CSM) factors, and work-relevant outcomes, we looked at the IP's impact on career optimism, career adaptability, and knowledge of the job market, as well as on employee- and organizationally-relevant outcomes. We analyzed data from 238 working professionals (57% female) using parallel multiple mediation analyses. The results revealed that the IP was negatively related to all work-relevant outcomes through decreased CSM factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 66 publications
1
26
0
3
Order By: Relevance
“…These results are in line with those found by Grubb Iii and McDowell (2012), Vergauwe et al (2015), Arkan (2016), and Neureiter and Traut-Mattausch (2016), in which people with higher levels of the IP tend to dedicate less time to activities or attitudes that transcend the formal academic role, given that the time employed in such actions could hinder the performance achieved in formal obligations and expose these individuals to the judgement of others.…”
Section: Cab1 Cab2 Cab3supporting
confidence: 91%
See 2 more Smart Citations
“…These results are in line with those found by Grubb Iii and McDowell (2012), Vergauwe et al (2015), Arkan (2016), and Neureiter and Traut-Mattausch (2016), in which people with higher levels of the IP tend to dedicate less time to activities or attitudes that transcend the formal academic role, given that the time employed in such actions could hinder the performance achieved in formal obligations and expose these individuals to the judgement of others.…”
Section: Cab1 Cab2 Cab3supporting
confidence: 91%
“…Similarly, Vergauwe et al (2015) identified a negative association between the IP and citizenship behaviors in Belgian business area professionals. Arkan (2016) and Neureiter and Traut-Mattausch (2016) collaborate the findings by verifying a negative relationship between the levels of impostor feelings and citizenship behaviors of employees in various sectors in Turkey and Austria.…”
Section: Establishment Of the Research Hypothesesmentioning
confidence: 84%
See 1 more Smart Citation
“…Although most of the studies were conducted in the USA 9, 10, 12, 13, 15-17, 21-32, 34-38, 42, 43, 45, 49-57, 61, 62, 64, 65, 67, 73 and Canada, 19,44,46,66,68 twenty-one studies evaluated populations in other countries including five in Austria, 39,[58][59][60]63 five in Australia/New Zealand, 20,31,70,71,74 four in Germany, 11,14,47,48,58 three in Iran, 33,40,41 two in the UK, 20,69 and one each in Belgium 72 and Korea. 73 Nearly all of the included studies were single-arm observational studies (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Career adaptability could help employees to synthesize their self-concepts into the collective organization, so they are motivated to take on off-duty activities on behalf of the organization. Another motivation to conduct OCBO is that adaptable employees have surplus capabilities and underused self-management resources to broaden task boundaries and engage in extra activities for their organization than those who have restricted career adaptability resources (Neureiter and Traut-Mattausch, 2016). Wang et al (2017) found that adaptable employees may expand task boundary and relational surroundings that facilitate the organization to better deal with change.…”
Section: Career Adaptability Task Performance and Organization-dirementioning
confidence: 99%